Serological estimation of values for urea, uric acid, and creatinine as a prognostic marker in oral submucous fibrosis patients: An institutional clinic-biochemical study - Vishal Mehrotra; Kriti Garg; Rahul Srivastava; Shazia Aslam; Jyoti Kiran; Vinayak Rai (SRM Journal of Research in Dental Sciences)
Background: The changes observed in the hematological/serological values and histopathological findings in oral submucous fibrosis (OSMF) patients may help in providing insight into the pathogenesis of this premalignant condition. Aims: The aim of this study is to estimate serum urea, uric acid, and creatinine in OSMF patients and compare them with habitual areca nut chewers and healthy controls and evaluate its potential as a prognostic marker in OSMF. Materials and Methods: A total of 150 patients were selected for the study and further categorized into Category I – included those subjects having OSMF, Category II – those subjects who had the habit of chewing betel nuts but had no features of OSMF, and Category III - comprised healthy controls with no habit history of chewing betel nut/tobacco. All variables from this study were analyzed by applying the analysis of variance (ANOVA) test and Chi-square test. Results: The results obtained from the present study showed statistically significant differences in serum urea, serum uric acid, and serum creatinine with various stages of OSMF. Conclusion: The serological estimation of urea, uric acid, and creatinine levels shows promise as a prognostic marker in OSMF patients. In the present study, elevated levels of these markers were associated with advanced disease stages and correlated positively with disease progression.